The Potential Hepatoprotective Activity of Allium paniculatum and Capparisspinosa on Thioacetamide induced Hepatotoxicity in Rats - Yusufoglu, Hasan; Soliman, Gamal A.; Abdel-Rahman, Rehab F.; Tatli-Çankaya, Irem; Alqasoumi, Saleh I.; S, SerapArabciAnul; Akaydin, Galip (Asian Journal of Biological and Life Sciences, 2015)
The aim of this study was to investigate the hepatoprotective effect of Allium paniculatum L. (A. paniculatum) and Capparisspinosa L. (C. spinosa) extracts in rats. Adult rats were divided into seven groups (n=6). The 1st (control) and 2nd (hepatotoxic) groups received the vehicle. The 3rd group received silymarin. The 4th - 7th groups received A. paniculatum and C. spinosa extracts at 2 dose levels (200 and 400mg/kg, respectively). Rats were administered the vehicle, silymarin or extracts orally for 21 days and simultaneously administered thioacetamide (TAA), one h after the respective assigned treatments(except the 1st group), every 72 h. At the end of the experimental period, all animals were sacrificed, blood samples were collected and serum was separated. Livers were dissected out for determination of their antioxidant status and for histopathological examination. Injection of thioacetamideelevated serum activities of liver enzymes; alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and γ-glutamyltransferase (γ-GT) in hepatotoxic group compared to normal controls. In the liver, significantly elevated level of malondialdehyde (MDA), lowered levels of reduced glutathione (GSH), catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD) were observed in hepatotoxic group.Treatment of rats with both extracts displayed hepatoprotective effect as evident by reduced serum activities of liver enzymes, as well as higher CAT, GPx, SOD activities and GSH concentration. The histopathological analysis suggested that both extracts obviously alleviated the degree of liver damage induced by TAA. In conclusion, A. paniculatumand C. spinosa attenuate hepatotoxicity induced by TAA.
Keywords: Allium paniculatum; Capparisspinosa; Hepatoprotective; Hepatotoxicity; Thioacetamide